Strengthening Early Childhood Learning Outcomes through Authentic Assessment of Students - Mastikawati Mastikawati; Hasan Baharun; Abd Hamid Wahid; Solehatin Solehatin; Robiatul Adawiyah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
The assessment process carried out in schools is traditional assessments that focus on cognitive, affective, and psychomotor aspects. The review should be able to assess all factors, namely attitudes, skills, and knowledge. This paper aims to describe authentic assessment in early childhood learning. The results of this study are a description of the original as a process of evaluating early childhood learning outcomes. This research was conducted at RA Alhanafiyah, located in the sub-district of Kotaanyar Probolinggo. The research technique uses qualitative methods by collecting data through observation, interviews, and documentation. Interviews were conducted on elements in the school, starting with the principal, four educators, and two guardians. The results showed that the authentic assessment was carried out in three stages: first, checklist, anecdotal evaluation, and evaluation of the work. The implications obtained from accurate estimates are applied to institutions that provide increased achievement in different categories such as achievements in cognitive, motor, language, religious and moral values, art, and social-emotional by looking at children's unique abilities.